Comparison of conventional and laboratory-scale alfalfa hay bales in small haystacks - Coblentz, W.K.; Fritz, J.O.; Bolsen, K.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A system for making laboratory-scale alfalfa hay bales was evaluated in two trials. In the first, conventional rectangular and laboratory-scale bales were made at each of seven different combinations of moisture and density. Laboratory bales were incubated between two parent conventional bales of identical moisture content and bale density. Laboratory bales remained different (P<.05) from parent conventional bales for most temperature-related storage traits. Agreement between bale types was better for most quality traits. To achieve closer agreement between bale types, a second experiment was conducted in which the laboratory bales were made at 1.0, 1.3, 1.6, and 2.0 times the density of the conventional bales. Agreement improved between laboratory bales of higher densities and conventional bales for most temperature traits. High-density laboratory bales had significantly greater acid detergent insoluble nitrogen values than conventional bales, particularly at the highest moisture level. These results implicate bale density as an important factor in heat damage to proteins in alfalfa hay.
Keywords: Beef; Hay; Alfalfa; Bale; Protein; Density